Bank Rakyat Malaysia: vision remains while mission is revisited - Khaliq, Ahmad; Kazmi, Azhar (I I U M Press, 2011)
The slogan, “of the people, for the people, by the people” comes home. Bank Rakyat Malaysia (BRM) offers a different kind of retail banking. Bank Rakyat underwent a drastic evolution from a cooperative system of management to a highly creative market entity ready to face the very aggressive competitive market forces of the Islamic banking and finance industry. The BRM was a cooperative bank before it entered the Islamic banking and finance industry. It needed to create a culture of change and flexibility to adapt to the changing external environments. The challenge was to remain consistent in its vision but revisit its mission. The consistency had to be maintained as it was in line with the founding fathers’ idea of serving its members. Thus the vision of serving its members was maintained while a new structure was created to aid efficient decision making and communication with stakeholders. This change subsequently facilitated the implementation of its growth strategies and planning activities, an imperative for its survival. All of this change was being effected while sustaining its image as a responsive, transparent and honest corporate citizen despite a host of issues and challenges that lie ahead.